2013
DOI: 10.1128/jvi.03571-12
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Forms of Vector Manipulation by a Plant-Infecting Virus: Bemisia tabaci and Tomato Yellow Leaf Curl Virus

Abstract: e For many insect-vectored plant viruses, the relationship between feeding behavior and vector competence may prove integral to an understanding of the epidemiology of the resulting plant disease. While plant-infecting viruses are well known to change host plant physiology in a way that makes them more attractive to vectors, viral manipulation of the vectors themselves has only recently been reported. Previous research suggested that the rapid spread of Tomato yellow leaf curl virus (TYLCV) throughout China ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
145
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 46 publications
11
145
1
3
Order By: Relevance
“…In addition, we found a positive relationship between TYLCV infection in tomato and the percentage of TYLCV-infected MED; in contrast, there was no relationship between plant health and the percentage of TYLCV-infected MEAM1. In sum, our findings are in accord with previous surveys (Pan et al 2012, Park et al 2012) and experimental work (Jiang et al 2000, Liu et al 2013a indicating that vector-plant transmission of TYLCV in Asia is predominantly associated with MED.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we found a positive relationship between TYLCV infection in tomato and the percentage of TYLCV-infected MED; in contrast, there was no relationship between plant health and the percentage of TYLCV-infected MEAM1. In sum, our findings are in accord with previous surveys (Pan et al 2012, Park et al 2012) and experimental work (Jiang et al 2000, Liu et al 2013a indicating that vector-plant transmission of TYLCV in Asia is predominantly associated with MED.…”
Section: Discussionsupporting
confidence: 93%
“…This hypothesis is supported by laboratory experiments (Pan et al 2012 and Þeld investigations (Chu et al 2007(Chu et al , 2010aSun et al 2009). In the laboratory, Pan et al (2012) and Liu et al (2013) found that TYLCV acquisition and transmission were greater with B. tabaci Q than with B. tabaci B. Field data concerning TYLCV and B. tabaci species in Shandong Province, China, are also consistent with our hypothesis that the rapid spread of TYLCV in China can be explained at least in part by the introduction and rapid spread of B. tabaci Q in China.…”
Section: Discussionsupporting
confidence: 87%
“…Tjallingii and Esch (1993)) and evidence for this is provided by elegant work using legume forisomes . That whiteflies utilise the same method has also been suggested in work by Liu et al (2013). The authors reported that B. tabaci infected with Tomato yellow leaf curl virus showed extensive salivation into sieve elements, which was interpreted as the virus affecting the ability of the whitefly to prevent sieve element occlusion to enhance the virus' transmission in watery saliva.…”
Section: Proposed Location Of Resistance To T Vaporariorum In L Pimmentioning
confidence: 72%